Primary balloon angioplasty for symptomatic, high-grade intracranial stenosis - Tomycz, Luke (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: In light of recent controversy about the safety and efficacy of intracranial stenting, we sought to evaluate our experience with primary balloon angioplasty for symptomatic, high-grade intracranial stenosis. METHODS: All intracranial angioplasty cases performed at Vanderbilt University Medical Center from 2006 to 2011 were retrospectively reviewed for degree of stenosis pre- and post-procedure. Immediate peri-procedural complications were evaluated as well as one-month and long-term outcomes. RESULTS: A total of 26 patients were included in the study with a mean age of 63.0 years and a mean follow-up of 350.2 days. The average pre-procedure stenosis was 71.2%. The immediate, average post-procedure stenosis was 46.6%, and the average post-procedure stenosis at last angiographic follow-up was 44.5%. Retreatment was required in only 3.8% of patients. The primary end-point of major stroke or death at 30 days was observed in 11.5%, and the overall intra-procedural complication rate was 7.7%. The incidence of stroke or death at last follow-up was 15.4%, which is comparable to the one-year stroke or death rate in the medical arm of the SAMPRISS trial. CONCLUSIONS: In this retrospective series, primary balloon angioplasty was found to be effective as a treatment option for symptomatic intracranial stenosis with the risk of stroke or death at 30 days higher than the medical arm of SAMPRIS but lower than the stenting arm. The one-year risk of stroke was comparable to that reported for the one-year outcomes in the SAMPRISS medical arm.